Some International Evidence on the Stochastic Behaviour of Interest Rates - TSE, Yiu Kuen (Institutional Knowledge at Singapore Management University, 1995)
This paper examines the stochastic behavior of short-term interest rates in eleven countries. Following Chan et al. (1992a), we consider eight stochastic models of short-term interest rates, all of which are nested within a discretized approximation to a differential equation. We use the generalized method of moments to estimate the model. The empirical results show that no single model can satisfactorily describe the stochastic structure of interest rates for all countries. On balance, if we classify the sample countries according to the size of the elasticity of variance of short-term interest rates, France, Holland and the USA belong to the group of high elasticity. In comparison, Australia, Belgium, Germany and Japan belong to the group of medium elasticity, while Canada, Italy, Switzerland and the UK belong to the group of low elasticity.